Synthesis of layered double hydroxides for anti-corrosion coatings on magnesium alloys: A review - Hafizuddin, Alias; Juliawati, Alias; Nasrul Azuan, Alang (Institute of Materials, Minerals & Mining, 2025)
Corrosion protection for magnesium (Mg) and its alloys is a critical aspect of enhancing their durability and extending their applications, particularly in automotive, aerospace, and biomedical fields. Mg alloys, known for their low density and high specific strength, are nevertheless highly prone to corrosion, which limits their widespread use. Surface modifications for Mg alloys remain the most appropriate strategy to overcome the rapid corrosion rate and improve the performance of Mg alloys. Despite extensive research on surface modifications, current approaches still face limitations. The potential solution of layered double hydroxide (LDH) films has garnered significant interest due to their ability to reduce the corrosion of Mg alloys by protecting outer surface, capturing corrosive anions, and combining with various anionic-based corrosion inhibitors. This review highlights the significant advancements made in corrosion protection for Mg alloys through the application of LDH, utilising hydrothermal treatment, co-precipitation and anion exchange in situ growth methods. This review also discusses how the optimisation of hydrothermal parameters has resulted in more uniform and adherent LDH layers and how synthesis parameters affect the structural and morphological properties of LDH films that lead towards surface superhydrophobicity.